Preparation method of nitrogen-doped silicon carbon negative electrode material

By introducing nitrogen atoms into the silicon-carbon composite material of the negative electrode material of lithium-ion battery and using porous carbon to provide expansion space, the structural damage caused by silicon volume expansion is solved, and the cycle stability and electrochemical performance of the battery are improved.

CN119890267APending Publication Date: 2025-04-25DONG JIAN CHU NA (SHANG HAI) JI SHU YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510090242.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The structure damage caused by volume expansion of the traditional lithium-ion battery negative electrode material, silicon, has limited its commercial application. Moreover, the preparation method of traditional silicon-carbon composite materials is complex and costly, making it difficult to achieve large-scale production.

Method used

By introducing nitrogen atoms into the silicon-carbon composite material, the number of holes in the material and the mobility of Li+ are improved, and porous carbon is used to provide expansion space for nanosilicon. Equipment such as automatic pressure reactors and kneaders are used to achieve uniform distribution of nanosilicon in porous carbon pores.

Benefits of technology

It improves the electrochemical performance of the material, enhances the cycle stability of the battery, and avoids the material structure damage caused by the expansion of silicon volume, providing new ideas for the preparation of the negative electrode material of high-performance lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251293080000071
    Figure BDA0005251293080000071
Patent Text Reader

Abstract

The invention provides a preparation method of a nitrogen-doped silicon carbon negative electrode material, which realizes preparation of a high-performance lithium ion battery negative electrode material through finely regulated chemical process steps. The method comprises the following steps: firstly, adding a nitrogen-containing dispersant into ethanol, and stirring until the nitrogen-containing dispersant is completely dissolved to form a dispersant solution; secondly, adding porous carbon and nano silicon into the dispersing agent solution, and uniformly stirring to form dispersion liquid; then, putting the dispersion liquid into a high-pressure reaction kettle, agglomerating the porous carbon and the nano silicon under the conditions of pressurization and high temperature, and drying to obtain a nitrogen-doped silicon-carbon negative electrode material precursor; and finally, mixing the precursor with asphalt, and sintering in a tubular furnace to obtain the nitrogen-doped silicon carbon negative electrode material. Through the method provided by the invention, the hole number of the material and the mobility of Li < + > can be effectively improved, and meanwhile, due to the existence of the pores of the porous carbon, the nano silicon has enough space expansion, and the damage to the material structure is avoided, so that the nitrogen-doped silicon-carbon negative electrode material with excellent performance is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a negative electrode material for a lithium ion battery, in particular to the preparation of a silicon-carbon composite material. Background Art

[0002] With the rapid development of new energy technologies, the demand for high-performance batteries is growing. Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, energy storage systems and other fields due to their high energy density and long cycle life. The key to improving battery performance lies in the improvement of electrode materials, especially the performance of negative electrode materials, which has a direct impact on the energy density and cycle stability of batteries.

[0003] Traditional negative electrode materials for lithium-ion batteries are mainly graphite, but their theoretical specific capacity is low, which limits the further improvement of battery energy density. In order to break through this limitation, researchers began to explore new negative electrode materials, among which silicon is considered to be an ideal negative electrode material due to its high theoretical specific capacity (about 4200mAh / g) and low potential platform (relative to lithium potential). However, silicon expands greatly during the charging and discharging process, resulting in material structure destruction and electrode performance degradation, limiting its commercial application.

[0004] In order to solve the problem of volume expansion of silicon negative electrode materials, researchers have proposed a variety of strategies, including combining silicon with carbon materials to improve structural stability. Silicon-carbon composite materials combine the high specific capacity of silicon with the good conductivity and chemical stability of carbon materials, which can effectively alleviate the volume expansion problem of silicon and improve the cycle stability of batteries. However, the traditional preparation method of silicon-carbon composite materials has problems such as complex preparation process, high cost, and difficulty in large-scale production. Summary of the invention

[0005] The present invention provides a method for preparing a nitrogen-doped silicon-carbon negative electrode material. The method realizes the preparation of a high-performance lithium-ion battery negative electrode material through finely controlled chemical process steps. The innovation of the present invention is that by introducing nitrogen atoms into the silicon-carbon composite material, the number of holes in the material and the Li + The mobility of the nano-silicon is increased, thereby enhancing the electrochemical performance of the material. The present invention uses porous carbon as a matrix, and its pore structure provides sufficient expansion space for nano-silicon, effectively avoiding the destruction of the material structure caused by the volume expansion of silicon during the charge and discharge process. The agglomeration of porous carbon and nano-silicon is promoted under pressure and high temperature conditions by using a high-pressure reactor to form a uniformly dispersed precursor, which lays the foundation for the subsequent sintering process.

[0006] The specific scheme of the present invention is as follows:

[0007] A method for preparing a nitrogen-doped silicon-carbon negative electrode material comprises the following steps:

[0008] (1) adding a nitrogen-containing dispersant into ethanol and stirring until the dispersant is completely dissolved to obtain a dispersant solution;

[0009] (2) adding porous carbon and nano-silicon into a dispersant solution and stirring to obtain a dispersion of porous carbon and nano-silicon;

[0010] (3) placing the porous carbon and nano-silicon dispersion into a high-pressure reactor, agglomerating the porous carbon and nano-silicon under pressure and high temperature, and obtaining a nitrogen-doped silicon-carbon negative electrode material precursor after drying;

[0011] (4) The nitrogen-doped silicon-carbon negative electrode material precursor and asphalt are mixed in a kneader and then sintered in a tubular furnace to obtain a nitrogen-doped silicon-carbon negative electrode material.

[0012] The porous carbon of the present invention provides nano-silicon embedded in the pores, which can alleviate the volume expansion of silicon particles in the negative electrode of the battery during charging and discharging, and prevent the silicon-carbon composite material from being pulverized and falling off on the electrode due to volume expansion.

[0013] The nitrogen-containing dispersant in step (1) is one or more of aziridine, polytetrafluoroethylene, polyvinyl pyrrolidone or citric acid.

[0014] In the step (1), the content of the nitrogen-containing dispersant in the ethanol is 0.5% to 10%.

[0015] In the step (2), the mass ratio of the porous carbon to the nano-silicon is 1-5:1-2, and the total mass of the porous carbon and the nano-silicon accounts for 20% of the mass of ethanol.

[0016] In the step (2), the size of the nano-silicon is 10-20 nm, and the pore size of the porous carbon is 20-30 nm.

[0017] In the step (3), the pressure in the high-pressure reactor is 5 to 10 MPa, and the high-pressure reactor is placed in an environment of 150 to 180° C. for 10 to 16 hours.

[0018] The asphalt in step (4) is one or more of coal asphalt, petroleum asphalt, natural asphalt, tar asphalt or modified asphalt.

[0019] In the step (4), the mass ratio of the nitrogen-doped silicon-carbon negative electrode material precursor to the asphalt is 5 to 10:1.

[0020] The kneading temperature in the kneading machine in step (4) is 150-200°C.

[0021] In the step (4), the sintering temperature in the tubular furnace is 800-1000° C., and the sintering time is 1-5 hours.

[0022] The present invention aims to provide a method for preparing nitrogen-doped silicon-carbon negative electrode materials, which can achieve uniform distribution of nano-silicon in the pores of porous carbon through high-pressure reactors and kneading machines, and improve the electrochemical performance of the material by doping with nitrogen atoms. This method can not only increase the number of holes and Li + It can not only increase the mobility of nano-silicon, but also provide sufficient expansion space for nano-silicon through the porous carbon pores, thereby avoiding the destruction of the material structure, providing a new idea for the preparation of high-performance lithium-ion battery negative electrode materials. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical scheme and technical effect of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention is clearly and completely described. The embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments. In conjunction with the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer; if the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0024] In the description of the present invention, the term "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0025] In the description of the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0026] It should be understood that the weight of the relevant components mentioned in the embodiments of the present invention can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present invention is proportionally enlarged or reduced, it is within the scope disclosed by the present invention. Specifically, the weight described in the embodiments of the present invention can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0027] In addition, unless the context clearly uses otherwise, the expression of the singular form of a word should be understood to include the plural form of the word. The term "includes" or "having" is intended to specify the existence of a feature, quantity, step, operation, element, part or combination thereof, but is not used to exclude the existence or possible addition of one or more other features, quantities, steps, operations, elements, parts or combinations thereof.

[0028] The technical solution adopted by the present invention is a method for preparing a nitrogen-doped silicon-carbon negative electrode material, and the specific implementation steps are as follows:

[0029] S1: adding the nitrogen-containing dispersant into ethanol and stirring until it is completely dissolved to obtain a dispersant solution;

[0030] S2 adding porous carbon and nano-silicon into the dispersant solution and stirring to obtain a dispersion of porous carbon and nano-silicon;

[0031] S3 puts the dispersion of porous carbon and nano-silicon into a high-pressure reactor, agglomerates the porous carbon and nano-silicon under pressure and high temperature, and obtains a nitrogen-doped silicon-carbon negative electrode material precursor after drying.

[0032] S4: After mixing the nitrogen-doped silicon-carbon negative electrode material precursor and asphalt in a kneader, the mixture is placed in a tubular furnace for sintering to obtain the nitrogen-doped silicon-carbon negative electrode material.

[0033] The present invention uses a high-pressure method to allow nano-silicon to enter the pores of porous carbon under the flow of solvent. The doping of N atoms can increase the number of material holes and improve the Li + The presence of porous carbon pores allows nano-silicon to have enough space to expand without destroying the overall structure of the material.

[0034] The nitrogen-containing dispersant in S1 is one or more of aziridine, polytetrafluoroethylene, polyvinyl pyrrolidone, citric acid, etc., preferably polyvinyl pyrrolidone (PVP) and / or citric acid, aziridine;

[0035] The content of the nitrogen-containing dispersant in S1 in ethanol is 0.5% to 10%, preferably 3 to 5%;

[0036] The mass ratio of the porous carbon and nano-silicon in S2 is 1-5:1-2, preferably 1:1;

[0037] The size of the nano-silicon in S2 is 10 to 20 nm, preferably 10 nm;

[0038] The pore size of the porous carbon in S2 is 20 to 30 nm, preferably 20 nm;

[0039] The total mass of the porous carbon and nano-silicon in S2 accounts for 20% of the mass of ethanol;

[0040] The pressure in the high pressure reactor described in S3 is 5-10MPa;

[0041] The reactor in S3 is placed in an environment of 150 to 180°C for 10 to 16 hours;

[0042] The asphalt in S4 is one or more of coal asphalt, petroleum asphalt, natural asphalt, tar asphalt, and modified asphalt, preferably coal asphalt;

[0043] The mass ratio of the nitrogen-doped silicon-carbon negative electrode material precursor and the asphalt in S4 is 5 to 10:1, and the preferred mass ratio is 10:1;

[0044] The kneading temperature in S4 is 150-200°C;

[0045] The sintering temperature of the tubular furnace in S4 is 800-1000° C., and the sintering time is 1-5 hours.

[0046] In order to enable those skilled in the art to clearly understand the implementation details and operations of the present invention, and to significantly demonstrate the improved performance of the embodiments of the present invention, the above technical solutions are illustrated by multiple embodiments below.

[0047] Example 1

[0048] A method for preparing a nitrogen-doped silicon-carbon negative electrode material, the specific implementation steps are as follows:

[0049] S1: Add 4 g PVP and 4 g citric acid into 200 g ethanol and stir until completely dissolved to obtain a dispersant solution;

[0050] S2: adding 20 g of porous carbon (pore size of 20 nm) and 20 g of nano-silicon (size of 10 nm) into the dispersant solution, and stirring to obtain a dispersion of porous carbon and nano-silicon;

[0051] S3 puts the dispersion of porous carbon and nano-silicon into a high-pressure reactor, reacts at a pressure of 5 MPa and 180° C. for 12 hours to agglomerate the porous carbon and nano-silicon. After taking it out, it is dried in a vacuum drying oven to obtain a nitrogen-doped silicon-carbon negative electrode material precursor.

[0052] S4: Mix 20 g of nitrogen-doped silicon-carbon negative electrode material precursor and 2 g of coal tar pitch in a kneader at 180°C, place in a tubular furnace and sinter at 800°C for 2 h to obtain a nitrogen-doped silicon-carbon negative electrode material.

[0053] Example 2

[0054] The difference from Example 1 is that aziridine is used as the dispersant.

[0055] Comparative Example 1

[0056] The difference from Example 1 is that porous carbon is not used but graphite is used instead.

[0057] Comparative Example 2

[0058] The difference from Example 1 is that nitrogen-free dispersants, polyethylene glycol and polyacrylic acid, are used.

[0059] Comparative Example 3

[0060] The difference from Example 1 is that no high-pressure reactor is used, and the dispersion of porous carbon and nano-silicon is directly kneaded with asphalt after drying.

[0061] Performance Testing

[0062] Button cells were made based on the silicon-carbon composite negative electrode materials provided in the above embodiments and comparative examples, and their electrochemical performance was tested.

[0063] The negative electrode slurry is coated on a copper foil, dried and rolled to obtain a negative electrode sheet; the electrolyte is a solution with LiPF6 and 10% FEC as electrolytes, with a concentration of 1 mol / L, wherein the solvent is a mixed solution of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene film.

[0064] In an argon glove box, the button cell was assembled on a Xinwei CT-4008Tn battery tester to carry out an electrochemical cycle performance test, with a charge and discharge voltage range of 0.01 V to 2.0 V and a charge and discharge rate of 0.1C.

[0065] In addition, the button cell was tested for capacity retention, and the specific test process was as follows: after formation, the cells were cycled three times at 0.1C (recording the average specific capacity Q1), 0.3C, 0.5C, 1C, 2C, and 3C, and then cycled three times at 0.1C (recording the average specific capacity Q2). Capacity retention = Q2 / Q1×100%.

[0066] Table 1

[0067]

[0068] It can be seen from the table that the material performance of the present invention has higher stability than the silicon-carbon negative electrode prepared by the traditional method.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a nitrogen-doped silicon-carbon negative electrode material, characterized in that: The steps include: (1) Adding a nitrogen-containing dispersant into ethanol and stirring until the dispersant is completely dissolved to obtain a dispersant solution; (2) adding porous carbon and nano-silicon into a dispersant solution and stirring to obtain a dispersion of porous carbon and nano-silicon; (3) placing the porous carbon and nano-silicon dispersion into a high-pressure reactor, agglomerating the porous carbon and nano-silicon under pressure and high temperature, and obtaining a nitrogen-doped silicon-carbon negative electrode material precursor after drying; (4) The nitrogen-doped silicon-carbon negative electrode material precursor and asphalt are mixed in a kneader and then sintered in a tubular furnace to obtain a nitrogen-doped silicon-carbon negative electrode material.

2. A method for preparing a nitrogen-doped silicon-carbon negative electrode material according to claim 1, characterized in that: The nitrogen-containing dispersant in step (1) is one or more of aziridine, polytetrafluoroethylene, polyvinyl pyrrolidone or citric acid.

3. A method for preparing a nitrogen-doped silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (1), the content of the nitrogen-containing dispersant in the ethanol is 0.5% to 10%.

4. A method for preparing a nitrogen-doped silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (2), the mass ratio of the porous carbon to the nano-silicon is 1-5:1-2, and the total mass of the porous carbon and the nano-silicon accounts for 20% of the mass of ethanol.

5. The method for preparing a nitrogen-doped silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (2), the size of the nano-silicon is 10-20 nm, and the pore size of the porous carbon is 20-30 nm.

6. The method for preparing a nitrogen-doped silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (3), the pressure in the high-pressure reactor is 5-10 MPa, and the high-pressure reactor is placed in an environment of 150-180° C. for 10-16 hours.

7. The method for preparing a nitrogen-doped silicon-carbon negative electrode material according to claim 1, characterized in that: The asphalt in step (4) is one or more of coal asphalt, petroleum asphalt, natural asphalt, tar asphalt or modified asphalt.

8. The method for preparing a nitrogen-doped silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (4), the mass ratio of the nitrogen-doped silicon-carbon negative electrode material precursor to the asphalt is 5-10:

1.

9. The method for preparing a nitrogen-doped silicon-carbon negative electrode material according to claim 1, characterized in that: The kneading temperature in the kneading machine in step (4) is 150-200°C.

10. The method for preparing a nitrogen-doped silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (4), the sintering temperature in the tubular furnace is 800-1000° C., and the sintering time is 1-5 hours.